ICT-policy in a geographical context - Sten Lorentzon (Netcom)
The introduction of ICT in Sweden is performed in the frame of centralistic governing and settlement structure characterized by activities located like islands in sparsely populated areas. Contrasts are evident between sparsely populated areas in the North and densely populated areas in the South. The development towards a more knowledge-intensive society tends to strengthen the role of Stockholm as the dominant Swedish node. In this context the use of ICT is seen as a tool to counteract tendencies towards regional imbalances. This paper focuses on the geographical conditions necessary to the use of ICT in Sweden and the efforts made on local, regional, national and international levels to support the use of ICT. The interplay of actors representing all levels is emphasized. In Sweden the local area authorities play an important role for launching and performing projects.